Kinerja Gabungan Kelompok Tani dalam Meningkatkan Pendapatan Petani Karet di Kecamatan Banyuasin III, Kabupaten Banyuasin, Provinsi Sumatra Selatan - Sriati Sriati; Rismarini Rismarini; Yunita yunita (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2022)
One such efforts to develop rubber business by forming a farmer group. This study aims to: (1) measure the level of performance the combined farmer group and the rubber farmer group, (2) measure the behavior rubber farmer, (3) calculate the production and income, (4) analyze the relationship the combined performance of the farmer group and the rubber farmer group with the behavior of rubber farmers, (5) analyzing the relationship behavior with production and income of rubber farmers. Research in the District Banyuasin III. This research method uses survey methods. Data from research and interviews made qualitatively presented in tabulation, mathematical calculations explained descriptively and Spearman Rank correlation analysis. Respondents are members of rubber farmers. The results of the study (1) the level of performance the combined farmer group high (98.00%) and the farmer group high (93.73%), (2) the behavior of farmers high (93.26%), (3) the average production (5,008 tons/year/cultivated) and average income of (Rp.33,600,059,122,-year/arable), (4) there is a significant relationship the performance of Gapoktan and Poktan with the behavior of rubber farmers, the value of Spearman Rank correlation coefficient 0.340 and 0.374 Î± 0.01, (5) there is no relationship behavior and production and income of rubber farmers with Spearman Rank correlation coefficient -0.032 and -0.070.